2010
DOI: 10.1111/j.1365-4632.2010.04596.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation in the ectodysplasin‐A (EDA) gene underlies X‐linked recessive nonsyndromic hypodontia

Abstract: A mutation identified in this study extends the body of evidence implicating the EDA gene in X-linked nonsyndromic hypodontia and supports the role of EDA-EDAR-EDARADD signaling in the morphogenesis of teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The most common HED is the X‐linked form (MIM 305100) resulting from mutations of EDA (MIM 300451) located on chromosome Xq12‐q13.1. It is rare that mutations in the same gene underlie an isolated non‐syndromic hypodontia that is not associated with anomalies in other ectodermal appendages or organs (Ayub et al, 2010). Mutations in the gene encoding EDAR (MIM 604095), located on chromosome 2q11‐q13, or EDARADD (MIM 606603), found on chromosome 1q42‐q43, cause autosomal recessive (MIM, 224900 and 614941, respectively) and dominant (MIM, 129490 and 614940, respectively) HED forms (Headon et al, 2001; Monreal et al, 1999), clinically indistinguishable from the X‐linked EDA form (Cluzeau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most common HED is the X‐linked form (MIM 305100) resulting from mutations of EDA (MIM 300451) located on chromosome Xq12‐q13.1. It is rare that mutations in the same gene underlie an isolated non‐syndromic hypodontia that is not associated with anomalies in other ectodermal appendages or organs (Ayub et al, 2010). Mutations in the gene encoding EDAR (MIM 604095), located on chromosome 2q11‐q13, or EDARADD (MIM 606603), found on chromosome 1q42‐q43, cause autosomal recessive (MIM, 224900 and 614941, respectively) and dominant (MIM, 129490 and 614940, respectively) HED forms (Headon et al, 2001; Monreal et al, 1999), clinically indistinguishable from the X‐linked EDA form (Cluzeau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] It can be seen in syndromic patients as well as nonsyndromic individuals. Several studies disclosed that seven genes are currently known to have a potential for causing nonsyndromic oligodontia: PAX9 [16] (paired box gene 9), MSX1 [17] (muscle segment homeobo × 1), EDA [18] (ectodysplasin A), AXIN2 [16] (axis inhibition protein), NEMO [19] (NF-kappa-B essential modulator), KRT17 [20] (keratin 17), and EDARADD [16] (EDAR-associated death domain). These types of abnormal incidents accompanying by class II division 2 malocclusion were known to be infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…It was first discovered as a candidate gene in an NSTA individual in 2001 ( Schneider et al, 2001 ) and was first identified in an X-linked inherited NSTA family in 2006 ( Tao et al, 2006 ). To date, 45 mutations in EDA have been linked to NSTA ( Schneider et al, 2001 ; Tao et al, 2006 ; Tarpey et al, 2007 ; Fan et al, 2008 ; Han et al, 2008 ; Li et al, 2008 ; Rasool et al, 2008 ; Mues et al, 2009 ; Song et al, 2009 ; Ayub et al, 2010 ; Mues et al, 2010 ; Arte et al, 2013 ; He et al, 2013 ; Nikopensius et al, 2013 ; Yang et al, 2013 ; Lee et al, 2014 ; Sarkar et al, 2014 ; Zhang et al, 2015 ; Gaczkowska et al, 2016 ; He et al, 2016 ; Shen et al, 2016 ; Bock et al, 2017 ; Martins et al, 2017 ; Yamaguchi et al, 2017 ; Zeng et al, 2017 ; Martínez-Romero et al, 2019 ; Parveen et al, 2019 ; Zhang et al, 2021a ; Biedziak et al, 2022 ; Yu et al, 2022 ), with missense mutations accounting for the majority (39/45). In addition, deletion mutations (3/45), altered splicing (2/45), and non-sense mutation (1/45) were also found in NSTA cases.…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%